2020
DOI: 10.1055/s-0040-1708522
|View full text |Cite
|
Sign up to set email alerts
|

Locking Plate Fixation for Canine Acetabular Fractures

Abstract: Objective The aim of this study was to document application of locking plates for stabilization of acetabular fractures along with complications and clinical outcomes. We hypothesized that complications and clinical outcomes would be comparable to historical reports using non-locking plate and screw constructs. Study Design Medical records of dogs presented with acetabular fractures at a single referral centre between 2010 and 2018 were reviewed. Cases surgically managed by open reduction and interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 28 publications
(53 reference statements)
2
15
1
Order By: Relevance
“…Other studies have hypothesized that the greater soft tissue exposure needed for perpendicular drilling when using locking implants could be related to a higher risk for injuries to occur. 18 similar to the numbers reported by Haine and colleagues (11/16). 16 All of our patients recovered function by the time of the first follow-up examination; this is a more immediate return to function than previously reported by Haine and colleagues where 3/17 patients presented with persistent deficits at follow-up examination.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies have hypothesized that the greater soft tissue exposure needed for perpendicular drilling when using locking implants could be related to a higher risk for injuries to occur. 18 similar to the numbers reported by Haine and colleagues (11/16). 16 All of our patients recovered function by the time of the first follow-up examination; this is a more immediate return to function than previously reported by Haine and colleagues where 3/17 patients presented with persistent deficits at follow-up examination.…”
Section: Discussionsupporting
confidence: 91%
“…5,16,17 Reported methods in cats include the following: figure-of-8 wire, screws and pins 17 ; figure-of-8 wire, screws and pins with polymethylmethacrylate 17 ; veterinary acetabular plates 5 and dynamic compression plate. 16 The stabilization of acetabular fractures with locking implants has recently been described in 17 dogs, 18 while previous reports in cats only included a total of 4 cases. 5,16 The objective of this study was to describe the clinical outcome and complications associated with the surgical application of locking implants for acetabular fractures in cats.…”
Section: Introductionmentioning
confidence: 99%
“…This clinical metrology instrument has been validated as a tool for assessing canine osteoarthritis with correlation to forceplatform data, 32 and its use has been reported in both dogs with elbow osteoarthritis 33 and to assess outcomes after articular fracture repair. 34 The LOAD scores were reported to be low in six of nine patients (range 1-10) and moderate in two of nine patients (11 and 12). Our mean follow-up of 42 months is similar to the 43 months reported by Gordon et al 35 All 13 elbows in that study developed post-traumatic osteoarthritis after HCF repair despite near anatomic reduction.…”
Section: Discussionmentioning
confidence: 84%
“…The decision to use the LOAD questionnaire to assess long‐term outcome was largely due to the retrospective nature of this case series. This clinical metrology instrument has been validated as a tool for assessing canine osteoarthritis with correlation to force‐platform data, 32 and its use has been reported in both dogs with elbow osteoarthritis 33 and to assess outcomes after articular fracture repair 34 . The LOAD scores were reported to be low in six of nine patients (range 1–10) and moderate in two of nine patients (11 and 12).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Moreover, the internal fixation screw benefits from strong shear forces and does not detach easily, which further promotes fracture healing. 20,21 This increased stability relative to double plate fixation is conducive to early initiation of functional recovery exercises, thus accelerating joint function restoration and improving prognosis. 22 The results of this study also showed that the fracture healing time of locking plate internal fixation group was significantly shorter than that of double plate internal fixation group, and the recovery of knee function was also better than that of double plate internal fixation group.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%